(untitled) (Quest Journal of Management and Social Sciences, 2023)
Purpose - Career adaptability is an important concept in organizational behaviour, especially in today’s quickly changing work environment, and firms worldwide face the challenge of retaining employees due to high turnover intentions. Drawing on Career construction theory, this study analyses the association between career adaptability and employee turnover intention in Nepalese private commercial banks. Design/Methodology/Approach -The explanatory research design examined the causal relationship between the career adaptability dimension and employee turnover intention. Cross-sectional data were collected from 380 respondents by using a convenience sampling technique. The data was analyzed quantitatively using structural equation modelling. Findings - Results show concern, curiosity, and confidence play a significant role in predicting turnover intention. Surprisingly, control does not seem to have a relevant influence on turnover intention. Research Limitations/Implications - The scope of this study is restricted to the banking professionals of Kathmandu Valley, self-reported bias, and cross-sectional data, which limits the generalizability of the findings. The study contributes to the expanding topic of career adaptability and turnover intention by underlining the significance of psychological factors in lowering turnover rates. Practical Implication- The application of this research is extensive, and organizations can use the findings to improve their recruitment practices and provide the necessary training for workers to adapt to changing careers while considering social and cultural factors, which can aid in retaining employees and enhancing organizational productivity. Originality/Value - To the author’s best knowledge, this study is one of the first attempts to examine the association between career adaptability and employee turnover intention in the banking industry by using Structural Equation Modelling and Career construction theory. Keywords - Concern, Control, Curiosity, Confidence, Employees Turnover Intention, Commercial Banks Paper Type: Research Paper